2021
DOI: 10.1111/jvs.13067
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia sieberishrubs have contrasting specific effects on understory species in Iranian steppes

Abstract: Questions (a) Are there contrasting short‐ and long‐term effects of shrubs on understorey species that may balance at the community level? (b) Are these effects due to the responses of different understorey species groups? (c) Are these effects contributing to community composition? Location An Artemisia steppe community in Golestan National Park (North‐East Iran). Methods We used both the removal and observational methods to separate short‐ from long‐term effects of Artemisia sieberi Besser on the cover of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…It seems that an increased taxonomic diversity in Artemisia patches and functional and phylogenetic diversity in Stipa patches are influenced by the presence of a wide range of plant species or by some specific plant species with different functional identities and distant evolutionary relatedness. However, some recent studies have shown negative or neutral effects of Artemisia patches on plant biodiversity structure, especially on taxonomic diversity (Bahalkeh et al, 2021 ; Rahmanian et al, 2021 ). These contrasting results are likely to be contingent on different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that an increased taxonomic diversity in Artemisia patches and functional and phylogenetic diversity in Stipa patches are influenced by the presence of a wide range of plant species or by some specific plant species with different functional identities and distant evolutionary relatedness. However, some recent studies have shown negative or neutral effects of Artemisia patches on plant biodiversity structure, especially on taxonomic diversity (Bahalkeh et al, 2021 ; Rahmanian et al, 2021 ). These contrasting results are likely to be contingent on different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the combination of species-specific effects of Artemisia on neighbors may result in the differences in lichen and annual species composition found from site to site. Bahalkeh et al (2021) found contrasting effects of A. sieberi on neighbor plants, and Jankju (2013) found facilitative to neutral effects of A. kopetdaghensis depending on climatic conditions. These different interactions of Artemisia could be explained by several factors.…”
Section: Tablementioning
confidence: 96%
“…Percentage cover of the Artemisia shrub ranged on average from 17.6%±3.0 (Alagol) to 25.5%± 8.8 (Bagh valley). Almeh valley is alluvial and contain the upstream deposits of stones, pebbles, clay with slopes below 5%, but Bagh valley contain the upstream tiny sediments with slopes below 2% (Bahalkeh et al, 2021), Alikhani consists of a gentle hilly landscape. Alagol includes small loess hills around the Alagol wetlands (Kakeh et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…For the Tibet Plateau, Michalet et al (2015) evidenced the occurrence of contrasting direct and indirect responses of forb species to the influence of dominant shrubs and grasses. However, because in their study the contrasting species-group level responses balanced each other, community-level responses in terms of forb biomass and richness were null or very weak (see also Wang et al, 2017Wang et al, , 2019Bahalkeh et al, 2021). Researchers argued that this should occur in species-rich communities from intermediate environmental conditions because these are known to include different functional strategies (Grime, 1973;Michalet et al, 2006).…”
Section: Introductionmentioning
confidence: 99%